Reclassification of the overlap syndrome of Behçet’s disease and antineutrophil cytoplasmic antibody-associated vasculitis in patients with Behçet’s disease - Tae Geom Lee; Jang Woo Ha; Jason Jungsik Song; Yong-Beom Park; Sang-Won Lee (The Korean Journal of Internal Medicine)
Background/Aims This study applied the 2022 American College of Rheumatology/European Alliance of Associations for Rheumatology (ACR/EULAR) criteria for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) to patients with Behçet’s disease (BD) to investigate the proportion and clinical implications of the reclassification to the overlap syndrome of BD and AAV (OS-BD-AAV). Methods We included 280 BD patients presenting with ANCA positivity but without medical conditions mimicking AAV at diagnosis. Demographic data, items from the 2014 revised International Criteria for BD and 2022 American College of Rheumatology and European Alliance of Associations for Rheumatology criteria for AAV, ANCA positivity, and laboratory results were recorded as clinical data at diagnosis. A total score ≥ 5 indicated microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA), whereas a total score ≥ 6 indicated a diagnosis of eosinophilic GPA (EGPA). Results The overall reclassification rate of OS-BD-AAV was 8.6%. Of the 280 patients, 16 (5.7%) and 8 (2.9%) were reclassified as having OS-BD-MPA and OS-BD-GPA, respectively; none were classified as having OS-BD-EGPA. ANCA, myeloperoxidase-ANCA (P-ANCA), proteinase 3-ANCA (C-ANCA) positivity, hearing loss, and interstitial lung disease (ILD) at diagnosis were more common in patients with OS-BD-AAV than in those without. ANCA positivity and ILD at BD diagnosis contributed to the reclassification of OS-BD-AAV. However, hearing loss was not considered a major contributor to BD due to its possibility of developing as a manifestation of BD. Conclusions To our knowledge, this is the first study to demonstrate the reclassification rate (8.6%) of patients with BD and ANCA results at diagnosis as OS-BD-AAV.